THE ESTIMATION OF NATURAL GROUNDWATER PROTECTABILITY IN UMAN DENDROLOGY PARK "SOFIIVKA" USING ARCGIS 8.1 - AKSOM, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
It is offered a spatial GIS analysis technique for groundwater natural security estimation for the dendrology park "Sofiivka". The GIS integration data algorithm for spatial analysis is submitted.